Regeneration and early tending of black locust (Robinia pseudoacacia L.) stands in the north-west of Romania - Nicolescu, Valeriu-Norocel (Array, 2019)
Background and Purpose: The aim of this study is to highlight the importance of black locust (Robinia pseudoacacia L.), a North American-originating tree species of major importance in Romania, in extreme site conditions such as sand dunes. In this respect, a Research and Development (R&D) project has been carried out in Carei-Valea lui Mihai Plain (north-west of Romania) since 2016. Materials and Methods: Three sub-compartments were selected in IV Valea lui Mihai Working Circle, Săcueni Forest District: two pure natural regenerations by root suckers of black locust at different ages (sub-compartments 3B and 52A%) and a mixed black locust - black cherry stand (sub-compartment 23D). Biometrical measurements and analyses as well as biomass estimations were performed. A thorough statistical analysis using the data on initial, extracted and residual trees/stands was also performed. Results: The main outputs of the project are as follows: (1) Black locust was established naturally by root suckers and the stocking of newly established stands can be as high as 50,000 suckers·ha-1; (2) The initial growth of black locust regeneration is quick and the young regeneration can close the canopy in 1-2 years, resulting in an appropriate dune fixation and wind erosion control; (3) The young pure or mixed black locust-dominated stands are left untended until the first cleaning-respacing (mean diameter 5-6 cm), when the stand shows high stocking/density and a wide variation in tree size. This intervention is from below, heavy (intensity over 25% by number of trees or basal area) and of negative selection type, removing mostly low Kraft’s class, dead or dying, and defective trees. Conclusions: This R&D project has shown the high potential of black locust to establish naturally by root suckers after a low coppice cut and stump removal, as well as the fast initial growth of regenerated black locust.